The Pursuit of Medical Care for Female Victims of Nonfatal Strangulation at the Time of Police Response - Wilkes, Nicole (Violence against women, 2023)
Survivors of nonfatal strangulation face a number of physical health consequences, some of which can be fatal if untreated. Despite the known health risks and connections to delayed fatalities, little is known about strangulation and victims’ pursuit of medical care. Using data collected from prosecutors’ case files (n = 143), this study attempts to understand what factors contribute to victims receiving medical attention following a nonfatal strangulation assault reported to police. Findings indicate that the suspect disrupting an emergency call increases the likelihood of the victim pursuing medical care. Implications are discussed.